A STRUCTURAL MODEL OF THE INFLUENCE OF SHAREHOLDING STRUCTURE AND BOARD CHARACTERISTICS ON EARNINGS MANAGEMENT OF LISTED COMPANIES IN THE STOCK EXCHANGE OF THAILAND: A MULTILEVEL AND INDUSTRY-LEVEL ANALYSIS - Boonchan, Suppakrit; Thangpreecharparnich, Pranom (RMUTT Global Business and Economics Review, 2026)
This study investigates the effects of ownership structure and board characteristics on earnings management among firms listed on the Stock Exchange of Thailand (SET) during 2019–2023. Secondary data was collected from annual reports and Form 56-1 of 447 companies (2,235 firm-year observations). The analysis employed multiple regression and multilevel structural equation modelling (SEM) to examine both direct and moderating effects. Research results reveal that institutional and foreign ownership significantly reduces earnings management, while managerial ownership increases it. CEO non-duality was found to mitigate earnings manipulation, whereas the proportion of independent directors and moderating interactions were not statistically significant. These findings suggest that robust governance mechanisms can restrain opportunistic managerial behavior, enhance financial transparency, and strengthen corporate accountability. The study provides theoretical contributions by integrating agency and resource-dependence perspectives and practical implications for regulators and investors seeking to improve financial reporting quality and sustainability in emerging capital markets.